Optical dispersion characterization of CZTS thin films prepared by sol gel at different annealing temperature - Ali Ismail Salih (Tikrit Journal of Pure Science)
Thin films of (CZTS) were prepared by the sol–gel method and annealed at a range of temperatures (500, 550, 600, 650oC) under ambient condition. X-ray diffraction chart shows a preferential direction along (112) which was an indacating to the Kesterite structure. The optical properties of annealing thin films were examined by UV-Vis spectroscopy, and the energy gap was determined by the Tauc method. The band gap values increase with increasing the annealing temperature. The dispersion of refractive  index of the thin film was analyzed by using the concept of single oscillator in Wemple-DiDomenico model. The average values of the dispersion energy (Ed) and the oscillator energy (Eo) of the interband optical transition were obtained, Ed≈23eV, Eo≈3.775eV and Eg≈2.15eV. The average value of the oscillator energy has a close value to that of the energy gap, for this work Eo≈1.737Eg. It has been concluded that, as the annealing temperature of the CZTS thin films increase the optical transmittance and  the energy band gap will be decreased, also there is a blue shift in the shortest optical wavelength of CZTS thin films λCZTS, from 605 to 475nm with increasing annealing temperature from 500 to 600oC.